PHYSIOTHERAPY IN FERTILITY TREATMENT - INSIGHT ON MERCIER THERAPY - BANU, SHANAZ; T , MURUGARAJ.; LOPAMUDHRA,; E, SHANMUGANANTH. (International Journal of Psychosocial Rehabilitation, 2020)
According to Indian Society of Assisted Reproduction States that infertilitycurrently affects 10 to 14 % of the Indian population, with higher rates in urban areas; nearly 27.5 million couples actively trying to conceive but suffer from infertility because of PCOS, endometriosis and menstrual irregularities. Since there is a decreased success rate for various assisted reproductive techniques; ‘Mercier therapy’ a physiotherapy regimen helps to improve the reproductive function. This study aimed to determine the effectiveness of Mercier Therapy; an innovative visceral manipulating technique that assists the fertility treatment. It is aquasi-experimental study design. 20 subjects following fertility treatment through oral medication were recruited with the reference from the gynecologist.Subject’s aged between 24 to 30 years and Diagnosed with PCOS were included. Subjects were collected through consecutive sampling manner and allocated in two groups of 10 each according through odd and even method; Group A(Controlled group) and Group B (Interventional group). Controlled group received normal fertility treatment alone. Interventional group received fertility treatment along with Mercier therapy, an innovative technique was given for a period of 5 months. After 5 months all subjects were investigated with ultrasound scan and observed for the ovarian follicle’sdevelopment. After5 months duration, 6 women from the Interventional group showed ovarian follicle development in ultrasound than those of 3 women in control group. Based on the above-mentioned result we conclude that Mercier therapy is valid in helping to women for cycle optimization. However further research is required for validation of the study.